2018
DOI: 10.2147/ppa.s175738
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations of investigating adherence to using offloading devices among people with diabetes

Abstract: Foot ulcers are a diabetic complication associated with significant morbidity, mortality, and amputation risk. Offloading devices prevent and heal foot ulcers, but adherence to using these devices is low. The reasons for nonadherence are unclear, and study results are difficult to compare due to methodological heterogeneity. This paper explores aspects of investigating adherence to using offloading devices among people with diabetes and provides recommendations for future studies, focusing on study designs, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…Although several studies included 'non-removable' devices, we recommend that adherence should always be assessed and reported as no device is strictly non-removable [61,62]. Rather, so-called non-removable devices imply different physical or psychological thresholds that patients can accept to prevent their future self from removing the device [63].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies included 'non-removable' devices, we recommend that adherence should always be assessed and reported as no device is strictly non-removable [61,62]. Rather, so-called non-removable devices imply different physical or psychological thresholds that patients can accept to prevent their future self from removing the device [63].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on footwear adherence have been criticized for not defining the conceptual framework, resulting in high heterogeneity, and for focusing on a narrow range of factors, typically those related to the patient, therapy and health condition [32]. This study included a wide range of factors and is the first study to use the entirety of the Health Belief Model to study the predictors of footwear adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Macfarlane and Jensen (13) reported that 12% (n = 6) of participants wore prescribed MGF > 80% of the time at home compared to 26% (n = 13) outside the home, while Waaijman et al (12) reported mean adherence of 61% at home compared to 87% adherence away from home for 107 participants with previous DFU, and this difference was statistically signi cant (p < 0.01). The challenge of comparing the ndings of the current study with previous research is that adherence is not frequently reported separately for indoor and outdoor use, however, this is important given the signi cant difference in reported adherence between these two conditions (24).…”
Section: Adherence To Mgfmentioning
confidence: 81%